2013
DOI: 10.1186/1477-7819-11-119
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bilateral oncocytomas of the native kidneys following renal transplantation: report of a rare case and review of the literature

Abstract: Renal oncocytomas are benign tumors of the kidneys, which are usually diagnosed postoperatively, due to differential diagnostic problems, from a sample of a renal cell carcinoma. The development of a renal oncocytoma in the native kidneys following renal transplantation is a very rare condition and only a few cases have been published in the world literature. In this case report we present a unique case of bilateral multifocal renal oncocytomas of the native kidneys in a female transplant recipient 6 years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Vernadakis et al (9) have reported bilateral oncocytomas of the native kidneys in a renal transplant recipient. Due to the close association between oncocytoma and RCC, as well as reports on immunological disturbances in RCC and oncocytoma patients, the hypothesis of immune system involvement in the pathogenesis of these two tumors appears to be reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Vernadakis et al (9) have reported bilateral oncocytomas of the native kidneys in a renal transplant recipient. Due to the close association between oncocytoma and RCC, as well as reports on immunological disturbances in RCC and oncocytoma patients, the hypothesis of immune system involvement in the pathogenesis of these two tumors appears to be reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral tumors make up 95% of cases of renal oncocytoma, and multiple tumors make up 5%. [ 3 ] Renal oncocytomas arise from the intercalated cells of the kidney's distal collecting tubules. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…They represent approximately 3–7% of all primary renal solid tumors and occur most frequently in males (1.6:1). [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Renal oncocytoma (RO) is the second most common benign renal neoplasm which arises from the intercalated collecting duct cells in the kidney [1, 2]. It has an estimated incidence of 3 to 7% of all primary renal masses [3, 4] and comprises 10 to 15% of enhancing small renal masses (≤4 cm in diameter) [5].…”
Section: Introductionmentioning
confidence: 99%